Study of workload and utilisation of Central Sterile Supply Department of a Tertiary care Teaching hospital - Kumar, Sunil; Yatoo, G H; Malhotra, Monica (Innovative Journal of Medical and Health Sciences, 2021)
Hospital acquired infection or “nosocomial infection” adversely affects both patients and hospitals. Impact of nosocomial infections ranges from increased length of hospital stay, emotional stress, disability, death of the patients as well as increased hospital cost for the patients and providers. Studies in India have reported nosocomial infection rates from 8% to 58 %. To combat these infections, hospital needs effective methods of disinfection and sterilization which has nowadays been centralized into a single department called Central Sterile Supply Department. In the study it was observed that the average Workload of Autoclaves per month is 194 and 18967 number of items were sterilized. Similarly, average cycles done per month on Plasma Sterilizer are 81 and 5516 items were sterilized on average in a month. In our study , the utilization coefficient of Autoclaves was found to be 75% while utilization coefficient of Plasma sterilizer was found to be 50 %.Hence both the equipments are adequately used above the efficiency co-efficient.